Factors affecting intention to breastfeed among Syrian and Jordanian mothers: a comparative cross-sectional study - Ababneh Alla; Khader Yusuf S; Khassawneh Mohammad; Al-Akour Nemeh; Haddad Azeiza M (BMC, 2010)
Abstract Background Breastfeeding is considered the ideal method of infant feeding for at least the first six months of life. This study aimed to compare breastfeeding intention between Syrian and Jordanian women and determine factors associated with breastfeeding intention among pregnant women in these two countries. Methods A cross-sectional design was used to collect data from1200 pregnant women aged 18 years and above (600 participants from each country). A self- administered questionnaire was used to collect data on socio-demographic characteristics and breastfeeding intention. Results Intention to breastfeed was reported by 77.2% of Syrian and 76.2% of Jordanian pregnant women. There was no significant difference in intention to breastfeed between Syrian women and Jordanian women. In both countries, women with a more positive attitude to breastfeeding, women with previous breastfeeding experience and women with supportive partners were more likely to intend to breastfeed. Syrian women with a monthly family income of more than US$200, younger than 25 and primiparous or having one child were more likely to report an intention to breastfeed their infants. Jordanian women with an education level of less than high school and not living with their family-in-law were more likely to intend to breastfeed. Conclusions In Syria and Jordan, a more positive attitude to breastfeeding, previous breastfeeding experience and presence of supportive husbands are associated with intention to breastfeed. These factors should be considered when planning programs designed to promote breastfeeding in these two countries.